Research on the influence of frequency control methods on the energy efficiency of an automated electric drive of a pumping station - Klendiy, P.; Fedirko, M.; Kamyshlov, V.; Dudar, O. (Energy and Automation, 2025)
Pumping units are widely used for pumping various liquids, and most of all in water supply and drainage systems. Water consumption is a random function of time during the day (day, evening, morning) and depends on the season (summer, winter or spring).The efficiency and cost-effectiveness of cold and hot water supply, heating, drainage and water treatment enterprises of cities, urban and rural areas can be significantly increased through automation and the introduction of regulated electric drives.The article considers methods for increasing the energy efficiency of an automated electric drive of a pumping station, developed on the basis of a frequency converter using a PID regulator and an MRS controller. Existing technologies for regulating pump performance, such as the use of throttle valves and frequency converters (FCs), are analyzed. To study the impact of frequency regulation with a PID regulator and a digital twin on the energy efficiency of pumping units, a simulation model has been developed in the Matlab application package.The conducted studies show that the use of frequency control ensures the maintenance of the required technological parameters of the hydro network, reducing energy consumption compared to throttling with an unregulated pump drive, since operation at constant speeds leads to significant energy losses, especially in partial load modes.The use of an MPC controller allows you to improve the quality of the regulation process compared to a PID regulator, thereby increasing energy efficiency, anti-cavitation effect, and predictive diagnostics of defects reduces unplanned downtime.The potential for reducing energy consumption and improving the efficiency of pumping stations when using such methods has been assessed. The main advantages and disadvantages of frequency control, as well as the prospects for the development of these technologies in the context of energy saving, have been identified.Key words: automated electric drive, water pumping station, frequency control, MPC, digital twin, PID regulator, energy efficiency